Human Rights in Latin America: post-pandemic key reflections. (Ágora Journal, 2022)
This article analyzes the geopolitical context in Latin America after two years of the declaration of the Coronavirus pandemic, which represented a political, economic and social challenge for the countries of the region. The actions of the Latin American governments were disparate in terms of coping with the effects of the expansion of the Covid-19 virus, which highlighted the crisis in the international order and in Latin America in particular. It is intended to conceptualize the current process of globalization, the treatment of Human Rights in the region during this period, as well as to rehearse some axes in the face of the challenges that will arise in the face of the post-pandemic.
Keywords: Globalization; Human Rights; Latin America; Geopolitics; Pandemic